Development of Praziquantel sulphonamide derivatives as antischistosomal drugs - Andrea Angeli; Marta Ferraroni; Fabrizio Carta; Cécile Häberli; Jennifer Keiser; Gabriele Costantino; Claudiu T. Supuran (Taylor & Francis Group, 2022)
The almost empty armamentarium to treat schistosomiasis, a neglected parasitic disorder caused by trematode flatworms of the genus Schistosoma, except Praziquantel (PZQ), urged to find new alternatives to fight this infection. Carbonic Anhydrase from Schistosoma mansoni (SmCA) is a possible new target against this nematode. Here, we propose new PZQ derivatives bearing a primary sulphonamide group in order to obtain hybrid drugs. All compounds were evaluated for their inhibition profiles on both humans and Schistosoma CAs, X-ray crystal data of SmCA and hCA II in adduct with some inhibitors were obtained allowing the understanding of the main structural factors responsible of activity. The compounds showed in vitro inhibition of immature and adult S. mansoni, but further optimisation is required for improved activity.